Selective Pre-leaching of Tellurium From Telluride-Type Gold Concentrate - Yang, Wei; Lan, Xuechen; Wang, Qian; Dong, Ping; Wang, Gang (Frontiers in Chemistry, 2021)
With a telluride-type gold ore flotation concentrate as the research object, the Na2S + NaOH collaborative leaching process was applied to selectively separate tellurium before the cyanide leaching of gold and silver. The effects of process parameters including the type of leaching agent, the amount of leaching agent, liquid-solid ratio, leaching temperature, and leaching time on the leaching rate of tellurium were investigated. The results showed that the tellurium leaching rate could reach 78.14% under the optimum conditions of −0.038 mm (95%) grinding fineness, 80 g/L Na2S concentration, 30 g/L NaOH concentration, 4:1 liquid-solid ratio, 80°C leaching temperature and 3 h′s leaching time. The kinetic analysis showed that the leaching process of tellurium from telluride-type gold concentrate was a mixed type of chemical reaction control and diﬀusion control. The grain parameter in the leaching process was 0.26263 and the apparent activation energy E = 17.12 kJ/mol. Tellurium could be pre-leached from the telluride-type gold flotation concentrate through the Na2S + NaOH alkaline leaching process to achieve the effective separation of tellurium from noble metals, which, when eliminating the adverse effects of telluride on the leaching of gold and silver, provides new ideas for the extraction of rare element tellurium.